Pengaruh Pemberian Pupuk Organik Cair (POC) dan Pupuk Anorganik Terhadap Pertumbuhan dan Produksi Bawang Merah (Allium Ascolonicum L.Varietas Bima) - Surya Handayani; Siti Hardianti Wahyuni; Meiliana Friska; Jumaria (Yayasan Perguruan Kampus, 2024)
Shallots are a horticultural commodity that has an important role in the Indonesian economy. The use of liquid organic fertilizer (POC) in shallot cultivation can reduce the use of excess inorganic fertilizer. The aim of this research was to determine the effect of applying liquid organic fertilizer (POC) and inorganic fertilizer on the growth and production of shallots. The research used a randomized block design (RAK) with two factors. The first factor is the POC dose (0, 16 ml, 32 ml), the second factor is the anosganic fertilizer percentage dose of 0%, 50% and 100%. POC is applied every week 8 times, while inorganic fertilizer is applied 7 days after planting (DAP) and 30 DAP. Data analysis used analysis of variance (ANNOVA) and DMRT further test. The results showed that giving POC and a combination of both fertilizers had no significant effect (P>0.05), while giving inorganic fertilizer had a very significant effect on the growth and production of shallots (P<0.01). Providing a 50% dose of inorganic fertilizer produced the tallest plant (38.21 cm), the highest number of leaves (47.53), the highest number of tubers (22.10), the heaviest wet tuber weight (150.05 g) and the heaviest dry weight (132.22 g). ). The effect of giving the best fertilizer on the growth and production of shallots was obtained at a dose of 50% inorganic fertilizer.